Effects of Atmospheric Circulation on Stream Chemistry in Forested Watersheds Across the Northeastern United States: Part 2. Interannual Weather Type Variability. Issue 13 (28th June 2021) - Suriano, Z. J.; Siegert, C. M.; Leathers, D. J.; Gold, A. J.; Addy, K.; Schroth, A. W.; Seybold, E.; Inamdar, S.; Levia, D. F.
Abstract: Using synoptic classification techniques, synoptic‐scale weather types associated with large exports of dissolved organic carbon and nitrate‐nitrogen in three forested watersheds in the northeastern United States are analyzed. In contrast to Siegert et al. (2021, https://doi.org/10.1029/2020jd033413 ; Part 1), which details the general synoptic conditions associated with stream chemistry variations, this study focuses on the long‐term frequency, trends, and global‐scale forcing mechanisms of individual, chemistry‐relevant, synoptic types. Nine individual types are identified as the most important to stream chemistry exports in northeastern watersheds during a 2.5‐year period of high‐frequency stream chemistry observation (2014–2016). Streamflow chemistry was the most influenced by Northwest Flow synoptic weather types in Vermont, cold front passages associated with Weak Westerly Flow types in Rhode Island, and Southwest Flow (SWF) types in Maryland. Each type provides unique atmospheric conditions that result in variations in precipitation, and thus chemical signals. From 1948 to 2017, the Arctic and North Atlantic Oscillations greatly influenced the interannual frequency of the analyzed synoptic types. When the indices were positively phased, SWF types were more frequent, while Northwest Flow and Weak Westerly Flow types were less frequent. Long‐term trends in synoptic type frequency are, inpart, due to documented changes in these teleconnection indices toward more positively phased configurations. As the climate continues to change into the 21st century, such associations may continue to drive large changes in synoptic type frequency, and thus watershed hydrology and biogeochemistry in the Northeast region. Key Points: Individual synoptic weather types uniquely influence the export of dissolved organic carbon (DOC) and NO3 solutes in watersheds of the Northeast United States The interannual frequency and precipitation signals of multiple chemistry‐relevant synoptic types exhibit long‐term linear trends Variations in synoptic type frequency, and thus stream chemistry, are partially forced by teleconnection indices, such as the North Atlantic Oscillation (NAO)